2020
DOI: 10.1021/acs.jnatprod.9b01107
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Synthesis of Veranamine, an Antidepressant Lead from the Marine Sponge Verongula rigida

Abstract: The natural product veranamine was isolated from the marine sponge Verongula rigida. It contains a unique heterocyclic scaffold and demonstrates in vivo antidepressant activity and selective affinity for 5HT2B and sigma-1 receptors. The first total synthesis of veranamine is reported. Our scalable synthesis offers veranamine in six steps and 25% yield via an unprecedented vinylogous Pictet–Gams pyridine formation strategy. Veranamine is a promising new lead compound for antidepressant drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The Verongula sponges exhibited the same plethora of SIAs and verongiabenzenoids [ 133 , 134 , 135 , 136 ] that could be found across much of the rest of the order Verongiida; however, a unique array of brominated tryptamine-derived alkaloids, merosesquiterpenoids and a benzonaphthyridine were also reported. As well as being new to the family Aplysinidae, these compounds were also previously unreported within the order Verongiida, and thus have no biosynthetic precedents within this order, making Verongula unique amongst its Verongiida counterparts [ 137 , 138 , 139 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Verongula sponges exhibited the same plethora of SIAs and verongiabenzenoids [ 133 , 134 , 135 , 136 ] that could be found across much of the rest of the order Verongiida; however, a unique array of brominated tryptamine-derived alkaloids, merosesquiterpenoids and a benzonaphthyridine were also reported. As well as being new to the family Aplysinidae, these compounds were also previously unreported within the order Verongiida, and thus have no biosynthetic precedents within this order, making Verongula unique amongst its Verongiida counterparts [ 137 , 138 , 139 , 140 , 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
“…Veranamine 71 had a moderate affinity for serotonin receptors and was therefore assessed for antidepressant activity in mice using the forced swim test. This alkaloid 71 showed antianxiety and antidepressant activity and selective affinity for 5HT2B and sigma-1 receptors [97]. 24) were isolated from the perennial rye grass Lolium perenne [98].…”
Section: Tricyclic Alkaloidsmentioning
confidence: 99%
“…The traditional system of medicine is the bedrock for several commercial drugs for depression and is based on natural products from various sources ( Baird-Lambert et al, 1982 ; England, 1998 ; Hu et al, 2002 ; Hedner et al, 2006 ; Kochanowska et al, 2008 ; Zhao et al, 2016 ; Kochanowska-Karamyan et al, 2020 ; Singla, 2021 ). There is substantial evidence on the antidepressant activity of metabolic extracts and metabolites isolated from various medicinal plants ( Farahani et al, 2015 ).…”
Section: Natural Products Against Depressionmentioning
confidence: 99%